2019
DOI: 10.1038/s41598-019-43421-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Disease Resistance in Banana Progenitor Musa balbisiana against Xanthomonas campestris pv. musacearum

Abstract: Banana Xanthomonas wilt disease, caused by Xanthomonas campestris pv. musacearum (Xcm), is a major threat to banana production in east Africa. All cultivated varieties of banana are susceptible to Xcm and only the progenitor species Musa balbisiana was found to be resistant. The molecular basis of susceptibility and resistance of banana genotypes to Xcm is currently unknown. Transcriptome analysis of disease resistant genotype Mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 68 publications
1
45
0
Order By: Relevance
“…Interestingly, Capana00g000272 (calcineurin B-like protein), Capana04g001405 (carboxylesterase), Capana09g000319 (aldehyde dehydrogenase) and Capana09g000326 (glycosyltransferase) were also specifically expressed in VI037601, and the expression of which was significantly up-regulated after Xcv inoculation ( S5 Table ), indicating that they might play an important role in response to Xcv infection in VI037601. Receptor-like kinases are key pattern recognition receptors in response to pathogens [ 50 ]. Our findings also showed that many receptor-like kinases were significantly differentially expressed in ECW and VI037601, such as G-type lectin S-receptor-like serine/threonine-protein kinase (Capana07g002260) and LRR receptor-like serine/threonine-protein kinase (Capana03g000831), which were up regulated in ECW and VI037601 post Xcv inoculation ( Fig 4 and S5 and S8 Tables).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Capana00g000272 (calcineurin B-like protein), Capana04g001405 (carboxylesterase), Capana09g000319 (aldehyde dehydrogenase) and Capana09g000326 (glycosyltransferase) were also specifically expressed in VI037601, and the expression of which was significantly up-regulated after Xcv inoculation ( S5 Table ), indicating that they might play an important role in response to Xcv infection in VI037601. Receptor-like kinases are key pattern recognition receptors in response to pathogens [ 50 ]. Our findings also showed that many receptor-like kinases were significantly differentially expressed in ECW and VI037601, such as G-type lectin S-receptor-like serine/threonine-protein kinase (Capana07g002260) and LRR receptor-like serine/threonine-protein kinase (Capana03g000831), which were up regulated in ECW and VI037601 post Xcv inoculation ( Fig 4 and S5 and S8 Tables).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the southern M. balbisiana might be feral, originating after the recent human introduction of the species in the region as a source of food, medicine, fibre, and animal fodder. M. balbisiana was known by locals in northern Vietnam because of its higher tolerance to cold, drought and potential plant diseases, encouraging its cultivation in other parts of the country [38,39,42]. The southern populations of M. balbisiana, especially VTN-S1, were also found close to cultivated varieties.…”
Section: Genetic Diversity In Musa Balbisiana Populationsmentioning
confidence: 99%
“…This bias was recently attributed to interspecific recombination and large structural variations between the A and B genomes, highlighting a complex origin of cultivated bananas with one or multiple backcrosses [33][34][35][36]. In contrast to cultivars only consisting of genetic information of Musa acuminata (AA, AAA, AAAA), the presence of the B genome has been associated with increased drought and cold tolerance [37][38][39][40], resistance to Xanthomonas wilt [41][42][43], and tolerance against banana weevils [44]. The availability of a high quality reference genome [45] and recent identification of large structural variations between A and B genomes [36] will aid in the development of more optimal breeding of banana cultivars and considerable research has been done on assessing the geographic distribution and genetic diversity of wild M. balbisiana populations [29,[46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Plants commonly harbour more than a hundred AP2/ERF transcription factors that generally have low sequence similarity and exert various functions, many of which are associated with resistance to various stress factors, which is especially true for the ERF group within the AP2/ERF family (Gutterson & Reuber, 2004;Licausi et al, 2013;Xie et al, 2019). Numerous studies have demonstrated that resistance to different pathogens, including several Xanthomonas campestris pathovars, is positively correlated with ERF expression levels in different plant species and increases upon ERF transgene overexpression (Gutterson & Reuber, 2004;Champion et al, 2009;Sherif et al, 2012;Licausi et al, 2013;Cacas et al, 2017;Tripathi et al, 2019). One of the type III effectors from Xanthomonas euvesicatoria has been shown to directly downregulate the ERF transcription factor in Solanum lycopersicum to promote susceptibility (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%